Optimization of rice husk hydrochar via microwave-assisted hydrothermal carbonization: fuel properties and combustion kinetics - Zulkornain, Muhammad Fikri; Shamsuddin, Abd Halim; Normanbhay, Saifuddin; Md Saad, Juniza; Ahmad Zamri, Mohd Faiz Muaz (Elsevier, 2022)
The optimization of rice husk hydrochar was carried out via microwave-assisted hydrothermal carbonization to find the optimum parameters for hydrochar production. Three optimized hydrochar was selected to find the best properties for solid biofuel application. The percentage difference between predicted and experimental values was below 10% for all optimized hydrochar. Hydrochar B (optimized for maximum high heating value) has the highest fixed carbon (29.86%), lowest volatile matter (54.6%), lowest ash (8.87%) and highest higher heating value (18.9 MJ/kg) compared to raw rice husk, hydrochar A (maximum solid yield) and hydrochar C (maximum solid yield and higher heating value). The result suggests that the optimized hydrochar produced is comparable to lignite and can be used as direct solid biofuel.